2018
DOI: 10.1111/1471-0528.15415
|View full text |Cite
|
Sign up to set email alerts
|

Severe group A streptococcal infections in mothers and their newborns in London and the South East, 2010–2016: assessment of risk and audit of public health management

Abstract: Objective We describe cases of invasive group A Streptococcus (iGAS) in mothers or neonates and assess management according to national guidelines, which recommend administering antibiotics to both mother and neonate if either develops iGAS infection within 28 days of birth and investigation of clusters in maternity units.Design Cross-sectional retrospective study. Setting and population Notified confirmed iGAS cases in either mothers or neonates with onset within 28 days of birth in London and the South East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…Our molecular decryption of GAS infection of the human decidua supports epidemiological conclusions for the necessity of maintaining and even increasing prophylactic measures (2,66) and the need to develop a vaccine to prevent life-threatening GAS infections such as puerperal fevers.…”
Section: Discussionsupporting
confidence: 65%
“…Our molecular decryption of GAS infection of the human decidua supports epidemiological conclusions for the necessity of maintaining and even increasing prophylactic measures (2,66) and the need to develop a vaccine to prevent life-threatening GAS infections such as puerperal fevers.…”
Section: Discussionsupporting
confidence: 65%
“…Women in the first 30 days of puerperium have a 20-fold increased risk of invasive GAS infection compared with non-pregnant women of reproductive age [8,9]. Invasive GAS infections in puerperium often present as endometritis or sepsis with a genital focus, but can also manifest at a non-genital site, and as GAS bacteraemia without a clear focus [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The source of invasive GAS infection in puerperium is often the woman's throat or that of a close contact [11]. However, healthcare workers carrying GAS are also a possible source, and maternity ward clusters of puerperal GAS infections occur occasionally [9].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this suggested mode of transmission from a close dweller with symptomatic GAS pharyngitis has been described in two past cases reviewed in this work [2,20], but these did not pursue microbiological evidence for In our case, earlier recognition of the mother's symptoms may have enabled prompt maternal antibiotic treatment and brought into consideration isolation of the neonate from the mother. Leonard et al [21] recently published a study on severe GAS infections in mothers and their newborns. In this study of 134 maternal and 21 neonatal invasive GAS infections, Leonard et al found that the median onset time for infection was 2 days postpartum for mothers and 12 days postpartum for neonates.…”
Section: Discussionmentioning
confidence: 99%